Gastroesophageal Reflux Caused Pharyngitis in Local Population A Comparative Clinical Study - Mukhtar Ibrahim, Salma Mumtaz, Sehar Gul Memon, Umer Saeed Ansari, Marium Munir Tunio, Saba Shuja Shaikh, Arslan Shuja, Naveed Shuja (Pakistan Journal of Medical & Health Sciences, 2023)
Practical implication: Through current study health awareness can be delivered in the local population. Keywords: Esophagus, Gastroesophageal reflux diseases, Heartburn, Regurgitation and Retrosternal pain.